2018
DOI: 10.1155/2018/2169036
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer and Mitochondrial Dysfunctions of the Adjunct Adipose Tissues: A Case Study

Abstract: Excess body weight has been causally linked to an increased risk of different cancer types, including colorectal cancer (CRC) but the mechanisms underlying this association are practically unknown. We investigate redox state-superoxide (SO) generation rate, activity of complex I in electron transport chain (ETC) of mitochondria and of dinitrosyl iron complexes by electron paramagnetic resonance; activity of matrix metalloproteinase (gelatinase) MMP-2 and MMP-9 by gel zymography of adipose tissues (AT) from 46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…More recently, research focus has shifted towards metabolic cross-talk as one of the integral aspects of cancer-adipose tissue two-way communication [ 214 , 215 ]. Several exciting studies, including our own, showed not only that metabolic support provided by adipocytes is instrumental for cancer progression and metastasis but that it is redox-sensitive [ [216] , [217] , [218] ] and obesity-mediated [ [219] , [220] , [221] ] ( Fig. 6 ).…”
Section: Cancer As a Metabolic Disease: Deciphering The Intriguing Relationship With Obesity Metabolic Syndrome And Diabetes Through Redomentioning
confidence: 99%
“…More recently, research focus has shifted towards metabolic cross-talk as one of the integral aspects of cancer-adipose tissue two-way communication [ 214 , 215 ]. Several exciting studies, including our own, showed not only that metabolic support provided by adipocytes is instrumental for cancer progression and metastasis but that it is redox-sensitive [ [216] , [217] , [218] ] and obesity-mediated [ [219] , [220] , [221] ] ( Fig. 6 ).…”
Section: Cancer As a Metabolic Disease: Deciphering The Intriguing Relationship With Obesity Metabolic Syndrome And Diabetes Through Redomentioning
confidence: 99%
“…Nowadays, methods allowing immediate monitoring of free radicals alone and in reaction with a complex system (for example cells and tissues) are very important and widely used (Burlaka et al, 2018;Bukhari et al, 2018;Borbat et al, 2001). These methods mainly include ESR and electromagnetic spin resonance, also called electron paramagnetic resonance spectroscopy, EPR.…”
Section: Esr (Electron Spin Resonance)mentioning
confidence: 99%
“…Liver resection remains the main strategy in case of primary malignancies and metastatic liver injury by colorectal cancer (CRC). The parenchyma sparing strategy in liver surgery has proven as an effective way of acute liver failure prevention, “small‐for‐size” liver syndrome, and oncological safety . Successful resection should be considered when the preserved part of the liver parenchyma has not only adequate blood inflow through the system of the hepatic artery and portal vein, but also effective drainage into the system of the inferior vena cava.…”
Section: Introductionmentioning
confidence: 99%
“…The parenchyma sparing strategy in liver surgery has proven as an effective way of acute liver failure prevention, "small-for-size" liver syndrome, and oncological safety. 1,2 Successful resection should be considered when the preserved part of the liver parenchyma has not only adequate blood inflow through the system of the hepatic artery and portal vein, but also effective drainage into the system of the inferior vena cava. That is why, avoiding venous congestion causing the dysfunction of regeneration processes and in the worst cases tissue necrosis considered a significant factor in liver interventions planning.…”
Section: Introductionmentioning
confidence: 99%